Overview the Seven Stars Rating in Hotel Industry - Subakti, Agung Gita (Bina Nusantara University, 2012)
Picking the right hotel can be tricky especially in todayâs world of multiple rating systems. A luxury hotel rating once topped out at five stars but in the war to snag vacationers certain hotels that sing tunes of opulence and luxurious pleasure have started to accumulate seven stars. Star rating systems vary from continentto continent, country to country, and in a country. Hotel ratings have become a subjective assessment of amenities depending on the hotel and location. But the big question that is how they rate a seven stars Hotel. What makes it different from five stars Hotel or any fine establishment alike. In this case, the author is over viewing some of the Hotels in the world that are known for its seven stars reputation and taking a closer look on how they get their reputation for being the most luxurious Hotels in the world.